Pengaruh Menonton Film Kartun Spongebob Squarepant di Televisi terhadap Prestasi Belajar Bahasa Indonesia Siswa Kelas V SD Negeri 067952 Medan Johor - Ulfah Sari Rezeki (Universitas Quality, 2017)
The study was conducted in order to determine the negative effects of watching cartoons on television Spongebob Squarepants the learning achievement of Indonesian students in class V SD Negeri 067 952 Medan Johor. The study populations were students of class V SD Negeri Johor Medan 067952 2011/2012 academic year as many as two classes for a total of 60 students. The sample in this study were 60 students or total unit population. The instrument used was a questionnaire as many as 10 of the questions that have been declared valid and reliable and documentation study (value of report cards). The sample were analyzed using statistical correlation Pearson Product Moment and t-test. The research found students habits of watching cartoons on TV Spongebob Squarepants classified as moderate with an average score of 19.5 and value questionnaire learning achievement of Indonesian students an average of 73.52, or quite enough. The hypothesis testing results obtained r xy = -0.269 and-t = -2.217. Results obtained determination coefficient calculation I = 7.24%. Thus, it can be concluded that there is a negative effect of watching cartoons on television on student achievement class V SD Negeri 067952 Medan Johor Academic Year 2011/2012. Habits students watch cartoon Spongebob Squarepants on TV had a negative impact of 7.24% on the learning achievement of Indonesian students with the regression equation Y = 86.463 - 0,6639X. It gives the sense that the more often or are accustomed students Spongebob Squarepants watching cartoons on TV, the lower the learning achievement of Indonesian students who achieved it.